Molecular phylogeny and morphology reveal a new species of Phanerochaete (Phanerochaetaceae, Basidiomycota) from Yunnan Province, China - Li, Yunchao; Yang, Xin; Zhang, Xunchi; Su, Jiangqing; Zhao, Changlin; Zhou, Hongmin (Phytotaxa, 2025)
Wood-inhabiting fungi play a crucial role in forest ecosystems as an important group of decomposers, found in living trees, dead standing trees, decorticated trunks, fallen branches, and manufactured wood. A new wood-inhabiting fungus Phanerochaete flavissima, belonging to the family Phanerochaetaceae, is described and illustrated based on the morphological characteristics and molecular data. Phanerochaete flavissima is characterized by annual, resupinate basidiomata with pale yellow to yellow hymenial surface, a monomitic hyphal system having the simple-septate generative hyphae, and ellipsoid, colorless, thin-walled basidiospores measuring 4.5–5.5 × 2.0–3.0 µm. The phylogenetic analyses based on ITS+nLSU rDNA sequences confirmed that the new species belongs to the genus Phanerochaete, and revealed that the new taxon is closely related to P. carnosa. A full description, illustrations, and phylogenetic analysis results of the new species are provided.